Making sense of evolution: Darwin, God, and the drama of life - Haught, John F. (Westminster John Knox Press, 2010)
Introduction -- Darwin -- Design -- Diversity -- Descent -- Drama -- Direction -- Depth -- Death -- Duty -- Devotion -- Deity